2012
DOI: 10.1002/jso.23097
|View full text |Cite
|
Sign up to set email alerts
|

Expression of estrogen receptors in gastric cancer and their clinical significance

Abstract: Our results suggest that the presence of ER-β in gastric cancer could have a protective effect against invasiveness of gastric cancer. Further studies are needed to clarify the role of ER-β in gastric cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 28 publications
2
70
2
Order By: Relevance
“…Consistent with our result, several studies also found that ERα cannot be detected in gastric cancer cell lines (46,47).…”
Section: Estrogen Protects Against Gastric Cancer Through Erssupporting
confidence: 93%
“…Consistent with our result, several studies also found that ERα cannot be detected in gastric cancer cell lines (46,47).…”
Section: Estrogen Protects Against Gastric Cancer Through Erssupporting
confidence: 93%
“…This distribution is not clearly explained by the differences in the prevalence of risk factors between the genders. There have been conflicting reports of the effect of sex hormones on the development of gastric cancer [15,16]. According to a meta-analysis by Camargo et al [15], a longer period of fertility and hormonal replacement therapy were each associated with decreased gastric cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies indicate there are large differences in gastric cancer risk between men and women. This difference may be explained by the presence of estrogen receptors in gastric tissue and cancers (65). Decreased sex hormone levels or the cumulative effect of other conventional risk factors for gastric cancer in postmenopausal women may explain the observed differences by menopausal status.…”
Section: Discussionmentioning
confidence: 99%